Affect toward the self and self-injury stimuli as potential risk factors for nonsuicidal self-injury. (February 2018) - Fox, Kathryn R.; Ribeiro, Jessica D.; Kleiman, Evan M.; Hooley, Jill M.; Nock, Matthew K.; Franklin, Joseph C.
Abstract: Few risk factors for nonsuicidal self-injury (NSSI) have been identified. This study investigated diminished aversion toward self-injury (i.e., NSSI, suicide/death stimuli) and self-criticism as unique NSSI risk factors. After terminating a treatment study, 154 adults with a recent and frequent NSSI history completed self-report and computer-based measures of psychopathology, implicit and explicit self-criticism, and implicit aversion to NSSI and suicide/death. Participants were then contacted 4 weeks later to test factors predicting NSSI frequency over this follow-up period. Diminished aversion toward NSSI stimuli and self-criticism significantly predicted NSSI 4 weeks later. These effects were unique from other theoretically important predictors, such as past week NSSI frequency and total number of NSSI methods used. Findings provide support that erosion of barriers to NSSI (e.g., aversion to self-injurious stimuli, decreased self-worth) may facilitate continued engagement in these dangerous behaviors. Results shed light on potential treatment targets for NSSI. Highlights: Few strong nonsuicidal self-injury (NSSI) risk factors have been identified. We tested three variables as NSSI risk factors over a 4-week follow-up period. Diminished aversion to NSSI stimuli predicted NSSI frequency beyond relevant factors. Self-criticism also uniquely predicted NSSI frequency beyond relevant factors.